Radical 1,4-aryl transfer in arylcarboxamides leading to phthalimides, biaryls and enantiomerically enriched beta-arylethylamines - Robertson, J; Palframan, M; Shea, SA; Tchabanenko, K; Unsworth, W; Winters, C (2008)
5-exo Cyclisation of vinyl-, aryl- and alkyl-radicals onto the aryl group of arylcarboxamides is followed by β-scission of the resulting spirocyclohexadienyl radicals with ejection of a carbamoyl radical. The fate of this radical depends on the substrate but, in the cases studied, either 5-endo cyclisation or direct reduction follows to give phthalimides, biaryls or β-arylethylamines. © 2008 Elsevier Ltd. All rights reserved.